Peran Kepala Sekolah Sebagai Edukator untuk Meningkatkan Mutu Lulusan Di SMA Negeri I Muara Bungo - Hamirul, Hamirul (Efektor, 2019)
This study aims to determine the role of the principal of SMA 1 Muara Bungo in maintaining the quality of graduates by using descriptive methods and qualitative approaches with 15 informants consisting of 10 teachers and 5 students of class XII using triangulation generated by the principal's policy in improving the quality of his role as an educator graduating students include: Implementing the teaching and learning process routinely, evaluating routinely, holding additional learning, carrying out Try Out activities. Obstacles faced by school principals in improving the quality of graduation of students are: Funding, Human Resources, Lack of motivation of students to participate in additional learning activities, Students are less serious in participating in additional learning activities. Efforts made by principals in improving the quality of student graduation include: Making control cards for students participating in afternoon tutoring activities, Motivating students on the importance of additional learning activities, Creating learning programs that are creative, innovative, and conducive, Raising funds from student guardians.